2020
DOI: 10.3389/fcimb.2020.588168
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Host Innate Immunity by Non-Coding RNAs During Dengue Virus Infection

Abstract: An estimated 3.9 billion individuals in 128 nations (about 40% of global population) are at risk of acquiring dengue virus infection. About 390 million cases of dengue are reported each year with higher prevalence in the developing world. A recent modeling-based report suggested that half of the population across the globe is at risk of dengue virus infection. In any given dengue outbreak, a percentage of infected population develops severe clinical manifestations, and this remains one of the “unsolved conundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…They virtually participate in all biological pathways, including cell proliferation, differentiation, apoptosis, autophagy, and tissue remodeling. sncRNAs are also essential to regulate host responses to viral infections ( Choudhuri, 2010 ; Beermann et al, 2016 ; Romano et al, 2017 ; Rajput et al, 2020 ; Wu et al, 2020 ). Among sncRNAs, the most widely studied sncRNAs are microRNAs (miRNAs), which are 18–24 nt in length, carry 5′ monophosphate and 3′ hydroxyl (3′-OH) ends, and generally regulate genes via the argonaute (AGO) platform ( Schwarz et al, 2004 ; Fabian and Sonenberg, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…They virtually participate in all biological pathways, including cell proliferation, differentiation, apoptosis, autophagy, and tissue remodeling. sncRNAs are also essential to regulate host responses to viral infections ( Choudhuri, 2010 ; Beermann et al, 2016 ; Romano et al, 2017 ; Rajput et al, 2020 ; Wu et al, 2020 ). Among sncRNAs, the most widely studied sncRNAs are microRNAs (miRNAs), which are 18–24 nt in length, carry 5′ monophosphate and 3′ hydroxyl (3′-OH) ends, and generally regulate genes via the argonaute (AGO) platform ( Schwarz et al, 2004 ; Fabian and Sonenberg, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed when using the top-5 most correlated genes (Figure S9 and Table S7). Accumulating evidence strongly suggested that dengue viruses and their hosts employ lncRNAs to modulate the outcome of infection in their own favor [ 11 ]. These results suggested that dengue viruses selectively suppress immune responses and cell cycle pathways in the cells it infects, that may have important consequences for virus infection and transmission.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to protein-coding genes, the majority of human genome is transcribed into non-coding transcripts, which play critical roles in regulating the expression of genes [ 8 ]. Several reported studies have suggested that non-coding RNAs (ncRNAs), such as microRNAs, siRNAs and long non-coding RNAs (lncRNAs) accomplish critical roles in DENV infection [ [9] , [10] , [11] ]. In particular, lncRNAs have been recognized to be associated with various biological processes and involved in diverse types of human diseases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18] Recent studies have found that miRNAs are widely involved in the regulation of immune and inflammatory responses by regulating the expression of cytokine genes as well as platelet biogenesis and degranulation. [19][20][21][22] A detailed, comprehensive understanding of exosomal miRNAs and their involvement in DENV infection will help to decipher the disease progression mechanism. In this study, we demonstrated the miRNA composition of the exosomes released during different stages of dengue infection.…”
mentioning
confidence: 99%